The Effect of Contextual Teaching Learning Method Toward Students’ Reading Skill at SMA Negeri 1 Panai Hilir - Laila Fitria; Muhammad Yusuf; Harianto II (International Journal of Educational Research Excellence (IJERE), 2024)
This study examines the efficacy of contextual teaching and learning (CTL) in enhancing reading proficiency among eighth-year students at SMAN 1 Panai Hilir. The research questions were as follows: (a) To what extent is the use of contextual teaching and learning (CTL) effective in improving students’ vocabulary? (b) What are the perceptions of students with respect to vocabulary acquisition through CTL? The research objectives were to ascertain (1) the efficacy of using CTL in improving students’ vocabulary and (2) students’ perceptions of vocabulary acquisition through CTL at the eighth-grade students of SMAN 1 Panai Hilir. The research employed a pre-experimental method with a pretest and posttest design, with the intention of providing a systematic expression or description of the data collected from a pre-experimental investigation. All eighth-year students at SMAN 1 Panai Hilir constituted the target population for this investigation during the 2024/2025 academic year. A purposive sampling approach was used to draw a sample from the population, with the resulting sample comprising 25 students. The sample was drawn from the lower class, with a total of 25 students. The research instruments consisted of a vocabulary test and a questionnaire. The vocabulary test was designed to assess the students' comprehension of the material, while the questionnaire aimed to gauge their perceptions. The research yielded two key findings: a pretest and a posttest. The results of the statistical analysis revealed that t-test values (21.823 > 2.064) were significantly different before and after the CTL intervention, indicating an improvement in vocabulary acquisition. This finding supports the hypothesis that the CTL method is an effective approach to enhancing vocabulary skills in 8th grade students at SMAN 1 Panai Hilir.